MENTAL HEALTH RESILIENCE OF MOTHERS CHILDREN WITH SPECIAL NEEDS - Nursanti, Siti (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
Families with children who have special needs encounter intricate difficulties in providing care and assistance to their children. The psychological well-being of mothers who provide care for children with special needs is a significant area of concern, given the pivotal role they play in the child's care and overall growth. The objective of this study is to comprehend the psychological fortitude of moms who breastfeed infants with special needs in Indonesia. In this study, a qualitative research methodology is employed, utilizing in-depth interview approaches to gather data from mothers who have children with special needs. The empirical evidence indicates that the resilience levels of these mothers exhibit considerable variation. Resilience is influenced by various elements, such as social support, awareness of the child's illness, and the capacity to cope with stress. These mothers exhibit resilience and the capacity to recover from daily demands and hardships. They depend on familial support, religious faith, companionship, and community, and cultivate efficient mechanisms for managing challenges. Despite experiencing significant levels of stress, these mothers demonstrate unwavering dedication to ensuring optimal care for their children.